The genome sequence of the jet ant, Lasius fuliginosus (Latreille, 1798) [version 1; peer review: 2 approved] - Liam M. Crowley (Wellcome Open Research)
We present a genome assembly from an individual female Lasius fuliginosus (the jet ant; Arthropoda; Insecta; Hymenoptera; Formicidae). The genome sequence is 256.2 megabases in span. Most of the assembly is scaffolded into 14 chromosomal pseudomolecules. The mitochondrial genome has also been assembled and is 18.75 kilobases in length.